China's Assimilationist Language Policy - Beckett, Gulbahar; Postiglione, Gerard (Routledge, 2013)
China has huge ethnic minorities - over 40 different groups with a total population of over 100 million. Over time China's policies towards minority languages have varied, changing from policies which have accommodated minority languages to policies which have encouraged integration. At present integrationist policies predominate, notably in the education system, where instruction in minority languages is being edged out in favour of instruction in Mandarin Chinese. This book assesses the current state of indigenous and minority language policy in China. It considers especially language policy in the education system, including in higher education, and provides detailed case studies of how particular ethnic minorities are being affected by the integrationist, or assimilationist, approach.